Analisis perhitungan pemungutan dan pelaporan pajak reklame atas pemasangan billboard pada CV Karya Wenang Manado - Rorong, Tessalonica; Budiarso, Novi Swandari; Datu, Christian (Riset Akuntansi dan Portofolio Investasi, 2024)
Regional tax is collected to fund the development of a region and demonstrates the community's active participation in financing government and regional development. Advertisement tax is imposed on taxpayers who promote products. This research aims to determine the calculation, collection, and reporting of Advertisement Tax at CV Karya Wenang Manado, in accordance with Manado City Regional Regulation No.2 of 2011 concerning Regional Taxes.  This study uses a qualitative descriptive research approach to investigate the calculation, collection, and reporting of Advertisement Tax at CV Karya Wenang. The findings indicate that the company adheres to Manado City Regional Regulation No.2 of 2011 regarding Regional Taxes, thus avoiding errors and sanctions.